EFFECT OF FOLIAR APPLICATION OF LICORICE ROOT EXTRACT AND POTASSIUM AND THEIR INTERACTION ON VEGETATIVE GRWOTH AND YIELD OF CAULIFLOWER (BRASSICA OLERACEA L.VAR.BOTRYTIS). HYBRID - SALEEM, JAMEEL S. MUHAMAD; SAEID, ABDUL JEBBAR I. (Journal of Duhok University, 2023)
The purpose of this investigation was to determine the impact of foliar spraying of Licorice root extract and Potassium on the quality (vegetative development and yield) of Cauliflower (Organza) hybrid during the fall semester of 2021 in (Agricultural Research Center) Malta Duhok, Kurdistan region, Iraq. The experiment was set up as a three-replication factorial experiment in a randomized complete block (R.C.B.D). The study’s findings demonstrated that foliar spraying of Licorice root extract at a concentration of 14 g.l-1 on Cauliflower increased the majority of the attributes investigated Spraying Potassium at a rate of 4ml.l-1 led to an increase in morale in the Cauliflower plant. Additionally, when given the maximum value in relation to the features investigated in the experiment, the interaction of treatments between Licorice roots extract at a rate of 14g.l-1 and Potassium at a level of 4ml.l-1